EVALUASI IMPLEMENTASI KTSP PADA PEMBELAJARAN GEOGRAFI SMA DI KOTA YOGYAKARTA - Mukminan . (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: An Evaluation of the Implementation of the SBC in Geography Instruction in SHSs in Yogyakarta City. This study aims to describe the imple- mentation of the School Based Curriculum (SBC) in geography instruction in senior high schools (SHSs) in Yogyakarta City in terms of teachers’ dimension, consisting of instructional programs, instructional steps, and learning outcome assessment. It was an evaluation study employing a model by Stake by comparing the instructtional processes conducted by teachers with the appropriate criteria. The population comprised 56 geography teachers in 11 state SHSs and 41 private SHSs in Yogyakarta City. The sample was 30% of the total schools selected by the school category (upper, middle, and lower) based on the results of the national assessment in geography in 2008. The data were collected through a questionnaire, observations, and documents and were analyzed using the qualitative descriptive technique. The findings show that the instructional programs, instructional steps, learning outcome assessment are in the good category. Keywords: instructional programs, instructional steps, learning outcome assessment